Mechanical properties analysis of underground municipal pipelines subjected to traffic loads - Liao, Yu; Fang, Li; Zhao, Yanan; Cheng, Zihua (Frontiers in Earth Science, 2026)
This study delves into the mechanical properties of underground municipal pipelines under traffic loads, utilizing numerical simulations to explore the dynamic response of pipelines at varying burial locations and assess their ultimate load-bearing capacity. A simulation model was constructed using the multi-physical FEM software, focusing on the stress behavior of shallowly buried pipelines subject to traffic loading. The findings reveal that the impact of traffic loads supersedes that of soil self-weight stress for shallowly buried pipes. Pipelines located be-neath the carriageway experience greater forces compared to those beneath sidewalks, with minimal influence of centerline offset at consistent burial depths. Notably, the top, bottom, and waist portions of the pipeline are identified as particularly vulnerable regions, with rotation of the maximum force axis observed during shallow burial and deviation from the road centerline. This research provides theoretical insights for optimizing the layout of pipelines beneath urban roads, en-suring their operational safety and sustainability.